Analysis of musculoskeletal disorders symptoms in professors of the University of Pernambuco – Petrolina Campus - José Pereira de Lima Júnior; Tarcísio Fulgêncio Alves da Silva (Revista Dor)
BACKGROUND AND OBJECTIVES:College professors are exposed to numerous pressure sources which affect their quality of life and professional activities. Notwithstanding, studies discussing musculoskeletal disorders in this population are still scarce in the literature. This study aimed at evaluating symptoms of work-related musculoskeletal disorders among professors of the University of Pernambuco – Petrolina Campus.METHODS:Sample was made up of 49 professors and to obtain musculoskeletal symptoms prevalence and typology, the Nordic Musculoskeletal Symptoms Questionnaire was used, as well as the visual analog scale to evaluate pain intensity.RESULTS:The prevalence of musculoskeletal symptoms was 85.7%, being that 64.3% have reported that symptoms are related to and worsen with teaching activities, being cases suggestive of work-related musculoskeletal disorders. Most affected anatomic region was lumbar spine (54.8%), followed by cervical spine (45.2%), shoulders (23.8%) and wrists/hands (23.8%). Most prevalent regions with severe pain were upper limbs (36.8%), lower limbs (32.0%) and spine (21.9%).CONCLUSION:The studied sample had a high prevalence of musculoskeletal symptoms and acknowledged that symptoms are related to and worsen with teaching activities, being suggestive of work-related musculoskeletal disorders.